Development of computer-based acoustic characterisation of medical phantom (IR) - Anis Nazihah Mat Daud (2014)
The aim of this research is to develop a computerised measurement system for acoustic characterisation of medical phantom. The method used is the adaptation of insertion technique and the introduction of the stepped shape design of sample into the system. The developed system consists of an ultrasonic pulser/receiver, two transducers, a digital oscilloscope, a thermometer and a computer. Special computer interfacing is used in the system software development. The resulted software display contains the connection and control panel, the display panel and the calculation panel. The block diagram for software algorithm contains the connection block, the signal acquisition display block, the analysis block and the help block. The performance of the system is tested on agar and poly(methyl methacrylate) (PMMA) samples for different positions from transmitter (0.00 to 90.00 mm), different shape of samples (rectangular and stepped shape of sample), different thicknesses of samples[(2.88 0.06), (3.15 0.08) and (6.03 0.07) mm for PMMA sample and (12.70 0.02), (24.56 0.02) and (30.94 0.02) mm for agar sample], different temperatures of medium (23.0, 24.0 and 25.0 oC), different frequencies of transducers (2.25, 5 and 10 MHz) and different densities of medium (878, 961 and 1000 kg m-3).The results indicate that the developed system is independent to the position of sample from the transmitter and it can be used to determine the acoustic properties of the medical phantom for different thickness of sample, temperature of medium, frequency of transducers and density of medium. The implication is that the developed system offers user-friendly procedure, yet producing reliable and consistent measurement results, which are comparable to the reference values.